2022
DOI: 10.1109/tg.2021.3078834
|View full text |Cite
|
Sign up to set email alerts
|

Requirements for Location-Based Games for Social Interaction

Abstract: Social interaction is part of the fabric of society, and is essential to challenge many types of social barriers. Locationbased games provide a means to foster such interaction in local communities. The design of such games is currently based primarily on designer experience and on literature on game design in general, and not on an understanding of user requirements. This article explores the preferences and desires of adolescents in neighbourhoods of Rotterdam South to socially interact with others and engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…It identifies commonalities across these games and provides 1) a list of key components for LBGs for social interaction in public space, 2) a software architecture containing such key components, and 3) a proof of concept illustrating how this software architecture is instantiated in the LBG "Secrets of the South", a game that has shown to provide opportunities for players to come together and interact in their neighbourhood [5,18,20]. This paper complements prior research of the authors on meaningful social interaction through location-based games [3,5,[17][18][19][20][21][22][23] by specifically focusing on requirements for a systems' architecture for LBGs for social interaction.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…It identifies commonalities across these games and provides 1) a list of key components for LBGs for social interaction in public space, 2) a software architecture containing such key components, and 3) a proof of concept illustrating how this software architecture is instantiated in the LBG "Secrets of the South", a game that has shown to provide opportunities for players to come together and interact in their neighbourhood [5,18,20]. This paper complements prior research of the authors on meaningful social interaction through location-based games [3,5,[17][18][19][20][21][22][23] by specifically focusing on requirements for a systems' architecture for LBGs for social interaction.…”
Section: Introductionmentioning
confidence: 88%
“…As part of a 4 year doctoral programme, initial design choices for the game were Players administer game play 1) to be played by children, 2) in their neighbourhood, 3) to involve everyone, and 4) to be fun [23]. Additional requirements were elicited from children during workshops designed to this purpose [17,19]. The next stage explored the functionality that needs to be included in a design and implementation for the promotion of social interaction [18,20].…”
Section: Proof Of Concept: the "Secrets Of The South"mentioning
confidence: 99%
See 1 more Smart Citation
“…This enables a different kind of engagement with the characters and brings life back into old stories. These experiences can also benefit individuals and communities increasing social interaction [2]. A study of theme parks in China also showed that audiences responded well to known stories with surprising elements [3].…”
Section: Interactive Location Based Experiences In Animationmentioning
confidence: 99%
“…The location-based entertainment industry is predicted to reach 21.42 billion dollars by 2028 [10]. They can provide a place for people to foster positive social interactions with family and friends [2]. However, new installations are often very expensive to build, utilising state-of-the-art technologies.…”
Section: Introductionmentioning
confidence: 99%